2020
DOI: 10.1002/jcp.29918
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Sox4 protects against myocardial ischemic injury by reduction of cardiac apoptosis in mice

Abstract: Sox4 participates in the progression of embryo development and regulation of apoptosis in tumors. However, the effect and mechanism of Sox4 in myocardial infarction (MI) remains unclear. Therefore, we aimed at examining the role and molecular mechanism of Sox4 in the process of cardiomyocytes apoptosis during MI. The expression of Sox4 were obviously increased both in MI mice and in neonatal mouse cardiomyocytes treated with H 2 O 2. Overexpression of Sox4 promoted cardiomyocyte apoptosis with or without H 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…SOX4 has been found to increase myocardial cells apoptosis and is regarded as a promising target for treating AMI [ 27 ]. In our present study, SOX4 was discovered to be the target of miR-132-3p and bind to miR-132-3p depending on its 3ʹUTR according to the analysis of Targetscan database.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SOX4 has been found to increase myocardial cells apoptosis and is regarded as a promising target for treating AMI [ 27 ]. In our present study, SOX4 was discovered to be the target of miR-132-3p and bind to miR-132-3p depending on its 3ʹUTR according to the analysis of Targetscan database.…”
Section: Discussionmentioning
confidence: 99%
“…The labeled cells were regarded as apoptotic cells. Finally, the fluorescence microscope (Olympus, Japan) was used to take photograph of positive cells within six different random views [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More and more studies have shown that SOX4 can participate in the development of malignant cancers such as breast cancer and gastric cancer by affecting cell growth, metastasis, and apoptosis (Ding et al, 2019;Song et al, 2019). A recent study showed that SOX4 expression was elevated in H 2 O 2 -induced cardiomyocytes, and its downregulation had a protective effect on cardiomyocytes injury (Zhang et al, 2021). Here, SOX4 was confirmed to be targeted by miR-590-3p.…”
Section: Discussionmentioning
confidence: 63%